Nonlinear Digital Encoders for Data Communications. - Vladeanu, Calin (FOCUS Series., 2014)
This book presents digital encoders for data communications. After an introduction on data communications and different sequences, the authors present the frey encoder as a digital filter followed by the trellis-coded and parallel turbo trellis-coded modulation schemes using nonlinear digital encoders. The book contains many numerical examples that complete the description of the analyzed schemes. Also, some performance simulation results are provided. Appendixes include demonstrations for the mathematical apparatus used throughout the book and some Matlab/Simulink source files used to ru.